Profesionalisme Guru Pendidikan Agama Kristen Pada Tingkat Sekolah Menengah Atas di Kota Manado Tahun 2018 - Agus lope Tindige; Marde Christian Stenly Mawikere (MAGENANG : Jurnal Teologi dan Pendidikan Kristen, 2020)
This article examines the professionalism of Christian ReligiousEducation Teachers at the Senior High School level in Manado City. Theresearch was conducted using qualitative methods which were built fromliterature research, observation and interviews.This study begins with research on the professionalism ofteachers, both teachers in general and Christian Religious Educationteachers which are based on the example of the life and ministry of theLord Jesus Christ as the Great Teacher. Then proceed with empiricalresearch on the form of professionalism of Christian Religious Educationteachers, the obstacles faced by Christian Religious Education teachers inincreasing their professionalism and the efforts of Christian ReligiousEducation teachers in overcoming obstacles to increase theirprofessionalism.The results of the study show that there is an opinion regardingprofessional teachers of Christian Religious Education at the high schoollevel in the city of Manado which have links to formalities such as aminimum bachelor's diploma, following the teacher certification process,education and training, understanding the curriculum and alliances withfellow teachers. The obstacle for a Christian Religious Education teacherin increasing his professionalism comes from external factors such as thelimited development costs and opportunities for developing ChristianReligious Education teachers themselves. Meanwhile, the efforts of aChristian Religious Education teacher in overcoming obstacles inincreasing professionalism are also external factors such as furtherstudies, mastery of the curriculum and skills in the preparation oflearning tools.With the results of this study, it is possible to recommendproposals for Christian Religious Education teachers, especially in thecity of Manado for the professional development of teachers using theAction Research model. This model provides opportunities for ChristianReligious Education teachers to be involved and as the main actors in thelearning process, they identify and find problems, and then explore,explore and find their own answers to problems they encounter in the 3field. The Action Research Model is a model that can be an alternativechoice to help teachers develop their professionalism